IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS XI - Yayon Adi Galung Sastria; Erry Hidayanto; Santi Irawati (Jurnal Kajian Pembelajaran Matematika, 2020)
The problem that arises in learning the material for sequences and series in class XI Accounting at An-Nuuru Tirtoyudo Islamic Vocational School is the low problem-solving ability. These indications are seen, among others, the lack of basic knowledge of students about mathematics, counting errors, errors in applying strategies, inability to translate problems in mathematical form, misinterpreting problems in mathematical concepts, and lack of understanding of problems that arise. The application of the Problem Based Learning (PBL) model is an alternative that can be done by teachers to improve mathematical problem solving abilities. This research is a Classroom Action Research (CAR) on the Implementation of Problem Based Learning (PBL) Models to Improve Problem Solving Ability of Class XI Accounting Students at SMK Islam An-Nuuru Tirtoyudo. The results showed that the application of the PBL model could improve mathematical problem solving abilities. The stage of orienting students to problems, among others, students can relate the problem to the knowledge they have, can determine the things that are known, and can determine the things that are asked. The stage of coordinating students to learn through the formation of study groups. The stage of guiding the investigation is done by going around each group to provide facilities to students who have difficulty. The stage of developing and presenting the work is done by asking students to present their work in the form of reports, photos, videos, and others. The stage of analyzing and evaluating problem solving is done by asking students to re-examine the process and problem solving results obtained.